2017
DOI: 10.1093/geronb/gbx134
|View full text |Cite
|
Sign up to set email alerts
|

Volunteering in the Community: Potential Benefits for Cognitive Aging

Abstract: To help advance the field, this review puts forward recommendations for future research, with an emphasis on the need for robust study designs and specific investigations into the nature and extent of the cognitive benefits of volunteering. Through that work, researchers can determine how a simple and accessible activity like volunteering can best be used to help reduce the burden of age-related cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 44 publications
5
50
1
1
Order By: Relevance
“…On the one hand, the finding echoes Tomioka et al [ 19 ] who reminded the need to understand the relationship between SP and cognitive function in specific contexts. On the other hand, by acknowledging the complex mechanisms that underlie SP’s influence on cognitive function, this study calls for future studies to test whether there is a gender-difference in specific paths, such as through neurological health or mental health [ 43 ], with more sophisticated research design.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the finding echoes Tomioka et al [ 19 ] who reminded the need to understand the relationship between SP and cognitive function in specific contexts. On the other hand, by acknowledging the complex mechanisms that underlie SP’s influence on cognitive function, this study calls for future studies to test whether there is a gender-difference in specific paths, such as through neurological health or mental health [ 43 ], with more sophisticated research design.…”
Section: Discussionmentioning
confidence: 99%
“…We have to remember that all our participants (regardless of group belongingness) volunteered to the study. Correlational studies have shown that voluntary work protects against cognitive aging (reviews: Anderson et al, 2014; Guiney and Machado, 2018; Proulx et al, 2018), so we cannot exclude the possibility that any new and voluntary engagement might be intellectually beneficial for elderly people. Overall, our findings do fit well with the research suggesting that post-training gains are within reach of older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Social participation among older adults across a range of community-based activities including clubs and groups have been shown to benefit sleep (Chen, Lauderdale, & Waite, 2016), cognitive function (Bowling, Pikhartova, & Dodgeon, 2016;Kotwal, Kim, Waite, & Dale, 2016), and mental health (Croezen, Avendano, Burdorf, & van Lenthe, 2015). Similarly, civic participation among older adults across a variety of volunteer activities has been associated with health benefits both physical (Anderson et al, 2014) and cognitive (Guiney & Machado, 2018). While there has been a proliferation of organizations and programs, such as Encore (https://encore.org) and Generations United (www.…”
Section: Active Aging Community Features and Older Generational Agementioning
confidence: 99%